2016
DOI: 10.1016/j.mimet.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pichia pastoris cellular material on polymerase chain reaction performance as a synthetic biology standard for genome monitoring

Abstract: Advances in synthetic genomics are now well underway in yeasts due to the low cost of synthetic DNA. These new capabilities also bring greater need for quantitating the presence, loss and rearrangement of loci within synthetic yeast genomes. Methods for achieving this will ideally; i) be robust to industrial settings, ii) adhere to a global standard and iii) be sufficiently rapid to enable at-line monitoring during cell growth. The methylotrophic yeast Pichia pastoris (P. pastoris) is increasingly used for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Consequently, we cultivated P. pastoris strain TK150 to high cell density and measured the level of bioconversion achieved. Figure details the typical growth profile observed during cultivation of P. pastoris cells in a 1 L Infors bioreactor, reaching wet cell weight (WCW) of 600 g/L using the cultivation regime reported by Templar et al Samples were taken immediately prior to the start of methanol feeding (indicated as M1 in Figure ) and then 33 h and 58 h after the start of methanol feeding.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, we cultivated P. pastoris strain TK150 to high cell density and measured the level of bioconversion achieved. Figure details the typical growth profile observed during cultivation of P. pastoris cells in a 1 L Infors bioreactor, reaching wet cell weight (WCW) of 600 g/L using the cultivation regime reported by Templar et al Samples were taken immediately prior to the start of methanol feeding (indicated as M1 in Figure ) and then 33 h and 58 h after the start of methanol feeding.…”
Section: Resultsmentioning
confidence: 98%
“…Cultivation in bioreactor was performed using a Multifors 1L device (INFORS HT). The Multifors 1L device has been reported previously to achieve OD 600 in the range of 800–1000 and DCW of 150–200 g L −1 during K. phaffii cultivation by Templar et al. (2016) and Wei et al.…”
Section: Methodsmentioning
confidence: 99%